KEPUASAN KONSUMEN TERHADAP KUALITAS PELAYANAN AGROWISATA BELIMBING KARANGSARI - Nur Mahandi Azis; Lintar Brilian Pintakami; Luhur Aditya Prayudi (Universitas Islam Balitar, 2021)
This study aims to determine the services provided, determine the level of customer satisfaction and determine the effect of service quality on the satisfaction of visitors to the karangsari star fruit agrotourism. The sampling technique in this study is non-probability. The number of respondents was 50 people. Primary data from the distribution of questionnaires to visitors and secondary data were obtained from agro data and village monographs. The data is displayed in the form of frequency tables, using Likert scales, validity tests, reliability tests, ordinal data transformations up to intervals. Based on the research conducted, the quality of service has an impact on visitor satisfaction, the majority of tourists state that they are quite satisfied with the quality of service provided by karangsari star fruit agrotourism. The ranking of tourists on this level of satisfaction is also the result of a comparison between the quality of the service they get and the costs they have to spend.